The influence of memory and life experiences in the rewriting of the Bible: Agency as a(n) unconscious feature in (re)translation - Sousa, Márcia Dias (2022)
This project aims to analyze how the Catholic Bible has been (re)translated in a particular creative writing process. The case study is Colleen Carroll Campbell’s autobiographical work My Sisters the Saints: a Spiritual Memoir, in which specific biblical excerpts have been integrated into the authorial discourse. The relation between translation and memory will be crucial in this analysis: on the one hand, the author was raised in a strong Catholic environment in which reciting the Bible was a daily habit. On the other hand, the biblical verses were conveyed in such a way as “to get the right feel” (as she confided in an interview), i.e. to accord with the (personal) narrative as a whole. That is to say that they were essentially based on her memories, even if that made her distance herself from the published, approved or well-established versions of the Catholic English Bible which she had defined as her major references. This paper focuses upon the notion of agency in order to examine how personal experiences can determine how an author chooses to (re)translate such “authoritative” texts as biblical verses, as well as the possible reasons and effects of the options taken – that is, the contours of the rewriting pursued.